A Rare Case of Diffuse Alveolar Hemorrhage Secondary to Acute Pulmonary Histoplasmosis - Kunal Grover; Hadeel Zainah; Shubhita Bhatnagar; Tricia Stein (Case Reports in Infectious Diseases)
Diffuse alveolar hemorrhage (DAH) is a rare presentation of acute pulmonary histoplasmosis. While histoplasmosis has been reported to cause hemoptysis and alveolar hemorrhage in children, the English language literature lacks any adult case reports documenting this association. We report a case of pulmonary histoplasmosis where the initial presentation was pneumonia with a subsequent diagnosis of DAH.